Atención al cliente en la floristería “entre flores y detalles Mayrita” en la ciudad de Babahoyo - León Torres, Kariela Jury (2022)
The present work is the result of a case study that has been carried out with the purpose of analyzing the customer service in the florist Entre Flores y Details Mayrita in the city of Babahoyo, with respect to the service provided by the establishment in question. Through the results that have been obtained, they show that the population of interest is dissatisfied with the service provided by the florist. In this way it has been possible to discover that the manager and her employees are not adequately performing their functions, allowing each consumer to feel dissatisfied when making their purchase or visiting the place. And in turn to be able to identify the critical problems that the establishment presents; also suggesting improvements in the training of personnel that guarantees the provision of a service according to the demands that may arise.